Evaluation of the Performance of Helmet Prototypes Fabricated from Acrylonitrile Butadiene Styrene Composites Filled with Natural Resource - Nikmatin, S.; Hermawan, B.; Irmansyah, I.; Indro, M.N; Kueh, Ahmad Beng Hong; Syafiuddin, A (MDPI AG, 2019)
The performance of helmet prototypes fabricated from acrylonitrile butadiene styrene composites filled with oil palm empty fruit bunch fibers was evaluated. The fibers were produced using a milling procedure, while the composites were fabricated using a single-screw extrusion. The physical characteristics of the produced fibers, which are water content, size, and density, were investigated. In addition, the mechanical properties of the produced helmets, including shock absorption, yield stress, frequency, and head injury criterion (HIC), were examined. The impact strength of the produced helmets increases with the rise of filler content. In addition, the helmets were also able to withstand a considerable pressure such that the transmitted pressure was far under the maximum value acceptable by the human skull. The present work also found that HICs exhibited by the investigated helmet prototypes fulfill all the practical guidelines as permitted by the Indonesian government. In terms of novelty, such innovation can be considered the first invention in Indonesia since the endorsement of the use of motorcycle helmets.